2021
DOI: 10.1038/s41598-021-91666-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Taurine ameliorates thioacetamide induced liver fibrosis in rats via modulation of toll like receptor 4/nuclear factor kappa B signaling pathway

Abstract: Liver fibrosis is a significant health problem that can cause serious illness and death. Unfortunately, a standard treatment for liver fibrosis has not been approved yet due to its complicated pathogenesis. The current study aimed at assessing the anti-fibrotic effect of taurine against thioacetamide induced liver fibrosis in rats through the modulation of toll like receptor 4/nuclear factor kappa B signaling pathway. Both concomitant and late taurine treatment (100 mg/kg, IP, daily) significantly reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 108 publications
2
16
0
Order By: Relevance
“…Taurine prevents inflammatory damage by acting on nuclear factor ‘kappa-light-chain-enhancer’ of activated B-cells (NFkB)/cyclooxygenase (COX), p38 mitogen-activated protein kinases (MAPK)—c-jun N-terminal kinase-dependent (JNK), and myeloid differentiation primary response 88 (MyD88) signaling mediated by toll-like receptor 4 (TLR-4). It reduces inducible nitric oxide synthase (iNOS), C-reactive protein (CRP), and is the marker of lipid peroxidation thiobarbituric acid reactive substances (TBARS) [ 65 , 66 , 67 , 68 ]. However, the primary benefits of taurine supplementation are derived from its antioxidative activities [ 30 , 61 , 69 , 70 , 71 ].…”
Section: Taurinementioning
confidence: 99%
“…Taurine prevents inflammatory damage by acting on nuclear factor ‘kappa-light-chain-enhancer’ of activated B-cells (NFkB)/cyclooxygenase (COX), p38 mitogen-activated protein kinases (MAPK)—c-jun N-terminal kinase-dependent (JNK), and myeloid differentiation primary response 88 (MyD88) signaling mediated by toll-like receptor 4 (TLR-4). It reduces inducible nitric oxide synthase (iNOS), C-reactive protein (CRP), and is the marker of lipid peroxidation thiobarbituric acid reactive substances (TBARS) [ 65 , 66 , 67 , 68 ]. However, the primary benefits of taurine supplementation are derived from its antioxidative activities [ 30 , 61 , 69 , 70 , 71 ].…”
Section: Taurinementioning
confidence: 99%
“…Liver AST, ALT, ALP and TB are frequently used as biomarkers of liver injury and diseases ( Bozdağ and Eraslan, 2020 , Datsko et al, 2020 , Koyuncuoğlu et al, 2020 , Li et al, 2020 , Sun et al, 2021 ). Additionally, previous experimental studies showed that these parameters were significantly increased in animals exposed to TAA ( El-Baz et al, 2019 , Dwivedi et al, 2020 , Gowifel et al, 2020 , Bogahawaththa et al, 2021 , El-Gendy et al, 2021 , Younis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 90%
“…TAA‐induced toxicity is thought to be strongly linked to the activity of free radicals 49 . During oxidative stress, the body uses its antioxidant defensive mechanisms such as CAT and SOD to reduce lipid peroxidation 50 .…”
Section: Discussionmentioning
confidence: 99%
“…TAA-induced toxicity is thought to be strongly linked to the activity of free radicals. 49 During oxidative stress, the body uses its antioxidant defensive mechanisms such as CAT and SOD to reduce lipid peroxidation. 50 As a result, the activity of these antioxidant enzymes rises throughout the early stages of TAA These inherent defensive mechanisms become greatly compromised and inadequate when the oxidative stress is excessive.…”
Section: Discussionmentioning
confidence: 99%